A comparison between GSA and IGSA for optimal allocation and sizing of DG and impact to voltage stability margin in electrical distribution system - Khatib, Tamer; Bujal, Noor Ropidah; Sulaiman, Marizan; Abdul Kadir, Aida Fazliana; El Tawil, Naji Ammar Mansour (Korean Institute of Electrical Engineers, 2021)
Optimal placement and sizing of Distributed Generation (DG) are essential for future power planning of distribution networks. The performance of Gravitational Search Algorithm (GSA) and an Improved version of Gravitational Search Algorithm (IGSA) are compared in solving the optimization problem. The multi-objective function optimization includes power loss minimization (Ploss), Minimum bus voltage (Vbusmin), and an average voltage total harmonic distortion (THDv) are considered in this optimization problem and the IEEE 13-bus and IEEE 69-bus radial distribution network were applied on this study. The benefits due to the optimal placement and sizing of DG include power loss reduction, minimization of total harmonic distortion, and improvement of bus voltages, especially the weakest bus in the distribution network. The impact of DG installation at the proposed location with the proposed sizing on voltage stability margin also presented. The results show the Voltage Stability Margin (VSM) for both real power (P) and reactive power (Q) at the weakest bus after DG have improvement with present of DG.